PREDICTING ROLE OF COGNITIVE FUNCTIONING ON POST-TRAUMATIC STRESS SYMPTOMS AMONG FEMALE BURN VICTIMS (Journal of Medical & Health Sciences Review, 2025)
The present study main objective was to examine the predicting role of cognitive functioning on post-traumatic stress symptoms among female burn victims. The burn damage often lead to substantial psychological suffering, with post-traumatic stress being one of the greatest emotional reactions followed by trauma. Whereas cognitive functioning may serve as a protecting reason that may reduce the post-traumatic stress responses in female burn victims. The study used a cross-sectional research design, where female burn victims were the sample of study selected by using purposive sampling technique. Standardized measures of cognitive functioning and post-traumatic stress symptoms were administered to measure the predictive relationship between variables. The results of regression analysis showed that cognitive functioning was the significant predictor of post-traumatic stress symptoms (F(1,198) = 51.23, p < .001). Further, the results exposed a significant negative predictive correlation between cognitive functioning and post-traumatic stress symptoms, confirming that worsen cognitive functioning increase the post-traumatic stress symptoms in female burn victims. The findings highlight the significance of promoting cognitive functioning in recovery programs to improve the emotional flexibility and reduce post-traumatic stress in female burn victims.